2017
DOI: 10.1080/17461391.2017.1343387
|View full text |Cite
|
Sign up to set email alerts
|

Combined individual scrummaging kinetics and muscular power predict competitive team scrum success

Abstract: Scrummaging is a major component of Rugby Union gameplay. Successful scrummaging is dependent on the coordination of the forward players and the strength of the eight individuals. The study aim was to determine whether individual scrummaging kinetics and other candidate factors associated with scrummaging performance discriminate team scrum performances. Sixteen club-level forwards (stature: 1.80 ± 0.1 m; mass: 99.0 ± 18.2 kg) were initially divided into two scrummaging packs. A total of 10 various scrum permu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(81 citation statements)
references
References 40 publications
0
81
0
Order By: Relevance
“…Participants ranged in mean age from 16.6 to 34 years old, with the majority in their early 20s. Twelve studies used the full pack [3,4,[7][8][9]12,14,15,[21][22][23][24], while fourstudies used the front row [11,25,26] and two used the tight five only [10,13]. Two studies recruited a mix of forwards and backs (Dobbs 2017;Wu et al 2006) [27].…”
Section: Demographic Characteristics Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants ranged in mean age from 16.6 to 34 years old, with the majority in their early 20s. Twelve studies used the full pack [3,4,[7][8][9]12,14,15,[21][22][23][24], while fourstudies used the front row [11,25,26] and two used the tight five only [10,13]. Two studies recruited a mix of forwards and backs (Dobbs 2017;Wu et al 2006) [27].…”
Section: Demographic Characteristics Of Samplesmentioning
confidence: 99%
“…Few studies quantified rugby playing experience of their subjects: Dobbs [27] had an inclusion criteria for university athletes to have played at least 6 months. Green, Dafkin, et al [21] studied amateur players with an average of 11 years of playing experience, and Clayton [24] sampled players with an average of 8.4 years. The national players Wu et al [20] studied had played for 9.1 years on average.…”
Section: Demographic Characteristics Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15] Individual force contributions Scrum contests are usually won by packs with larger combined compressive forces. [23] Assessments of team scrummaging have identified the contribution of various playing positions in terms of the total scrummaging forces. Interestingly, the front rows contribute the most force, namely between 42% -46%, and locks generate between 21% -37%, respectively.…”
Section: Kineticsmentioning
confidence: 99%
“…[45] Therefore, it is not surprising that researchers have shown significant relationships between scrum force and combined pack mass. [10,[13][14][15][16]20,24,30] In the only study to have considered a combined power metric, Green et al [23] demonstrated that winning scrums also had significantly higher combined vertical jump heights.…”
Section: Muscular Strength and Powermentioning
confidence: 99%